Factors that impact the adoption of online food delivery services by urban consumers in South Africa - Capri, Talga (My University, 2021)
Online Food Delivery is defined as the process of ordering food from a website or application for the following categories; fresh produce and groceries, readymade meals or “take-aways or meal kits (Hirschberg, Rajko, Schumacher, & Wrulich, 2016). Online Food Delivery (OFD) services offers consumers convenience of access and time savings but not all consumers may trust OFD services and may perceive risks that can undermine OFD adoption and use. This research examined the factors influencing consumer adoption of OFD services among urban consumers in South Africa. This study followed a positivist paradigm and developed an extended Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model comprising twelve hypotheses. A selfadministered online cross-sectional survey was used to gather the data from a convenience and snowball sample of urban consumers drawn from a local University and the researcher’s professional network. A final usable sample of 180 consumers was available for analysis. The sample represented an adequate number of both male and female respondents, higher income earning groups, mainly over the age of 35, from multi-individual households with access to the requisite technologies, and who were familiar with OFD purchasing. The discriminant and convergent validity of constructs as well as the reliability of the construct measures was confirmed, except for the UTAUT2 construct of habit which was dropped from the model. Correlation and regression analysis was performed to confirm the strength and direction of the relationships between the proposed construct. Results supported performance expectancy, effort expectancy, social influence and trust as the most significant factors driving OFD adoption. These findings have implications for practice such as strategies around 1-Click ordering, intuitive application navigation, continuous social engagement methods, rewards, loyalty programs, maintaining quality and freshness of meals and an efficient delivery service. Suggestions for future research are provided.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Online Food Delivery (OFD); Online retail; e-Commerce; University of the Witswatersrand, Johannesburg; SDG-8: Decent work and economic growth